Report of a meeting between the Prime Minister, the Mining Association and Miners Federation, 23 April 1926 (page 27)
1926-04-23 "Report of a meeting between the Prime Minister, the Mining Association and Miners Federation, 23 April 1926 (page 27)" [g0492027.jpg], 23 April 1926, Trades Union Congress